2001
DOI: 10.1074/jbc.m102382200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Transforming Growth Factor β Signaling in Smad2- and Smad3-deficient Fibroblasts

Abstract: A prominent pathway of transforming growth factor (TGF)-␤ signaling involves receptor-dependent phosphorylation of Smad2 and Smad3, which then translocate to the nucleus to activate transcription of target genes. To investigate the relative importance of these two Smad proteins in TGF-␤1 signal transduction, we have utilized a loss of function approach, based on analysis of the effects of TGF-␤1 on fibroblasts derived from mouse embryos deficient in Smad2 (S2KO) or Smad3 (S3KO). TGF-␤1 caused 50% inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
350
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(390 citation statements)
references
References 43 publications
(73 reference statements)
35
350
3
2
Order By: Relevance
“…For example, TGF-β1 mRNA auto-induction is thought to have a beneficial role in cardiac wound healing after ischemic injury [44] , whilst auto-induction of TGF-β1 at the site of injury in the proximal tubule may result in a positive feedback, where sustained cytokine production may accelerate EMT and increase the generation of myofibroblasts thus promoting and exacerbating fibrosis. A correlation between Smads and AP-1 has also been suggested following elegant studies performed in a mouse model of unilateral ureteric obstruction and in fibroblasts obtained from Smad2 and Smad3 knockout animals [45][46]. These studies confirmed not only a correlation between Smad signalling and TGF-β1 auto-induction, but further demonstrated that the relationship depended on the presence and activation of Smad3.…”
mentioning
confidence: 63%
“…For example, TGF-β1 mRNA auto-induction is thought to have a beneficial role in cardiac wound healing after ischemic injury [44] , whilst auto-induction of TGF-β1 at the site of injury in the proximal tubule may result in a positive feedback, where sustained cytokine production may accelerate EMT and increase the generation of myofibroblasts thus promoting and exacerbating fibrosis. A correlation between Smads and AP-1 has also been suggested following elegant studies performed in a mouse model of unilateral ureteric obstruction and in fibroblasts obtained from Smad2 and Smad3 knockout animals [45][46]. These studies confirmed not only a correlation between Smad signalling and TGF-β1 auto-induction, but further demonstrated that the relationship depended on the presence and activation of Smad3.…”
mentioning
confidence: 63%
“…In normal fibroblasts, SMADs function as essential cytoplasmic effectors for TGF␤ stimulation of collagen synthesis, as well as that of CTGF (40) and of TGF␤ itself (41). Genetic targeting of the SMAD3 locus protected null mice from the development of radiationinduced fibrosis, indicating the fundamental physiologic role of SMAD3 in processes of tissue repair and fibrosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…A dramatically reduced level of phospho-JNK was seen in TGF-b-treated S3KO cells compared to S3WT MEFs (Figure 1b Immunoblotting was performed with 20-50 mg of samples using Tris-Glycine gels (Invitrogen, Carlsbad, CA, USA), 0.2 mm Nitrocellulose (Amersham, Piscataway, NJ, USA) and incubated with primary antibodies against Phospho-JNK, Phospho-ERK, total JNK and total ERK (all Cell Signaling, Danvers, MA, USA) followed by anti-rabbit HRP secondary antibody (Jackson ImmunoResearch Laboratories, West Grove, PA, USA) and chemiluminescence (ECL Plus, Pierce Biotechnology Inc., Rockford, IL, USA) was detected by films (Kodak MR, Sigma-Aldrich, St Louis, MO, USA) or digital imager (AlphaInotech, San Leandro, CA, USA). Primary mouse embryonic fibroblasts (b-d) were isolated from wild-type (S3WT), Heterozygote (S3Het) and knockout (S3KO) embryos between 12 and 16 days of gestation (Piek et al, 2001), propagated in Dulbecco's-modified Eagle's medium (DMEM) (Hyclone, Logan, UT, USA) supplemented with 10% fetal bovine serum (FBS) (Hyclone) and 1% penicillin-streptomycin (Gibco, Grand Island, NY, USA), grown to confluence and used between 2 and7 passages for all assays. Blots are representative of atleast three independent experiments.…”
Section: Tgf-b Signaling Via the Mapk Is Perturbed By Absence Of Smad3mentioning
confidence: 99%